1990
DOI: 10.1159/000168177
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of Radiocontrast Agents in Rats: A New Model of Acute Renal Failure

Abstract: The objectives of this study were first to develop a reproducible and reversible model of acute renal failure following contrast medium infusion in the rat; second to use that method to compare the nephrotoxicity of low- and high-osmolar contrast agents. Contrast media or saline were perfused in the aorta while a clamp was applied on the aorta just above the renal artery. Three minutes of renal ischemia with or without infusion of isotonic saline induced no change in serum creatinine and a slight and transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 17 publications
5
32
0
Order By: Relevance
“…Our results regarding the effect on renal function seems to be in accordance with another series of experiments (34,35). In an ischemic rat model it was found that intra-aortic injections of gadopentetate and diatrizoate, both with an osmolality of about 2.0 osmol/kg water, caused a similar decrease in GFR measured as creatinine clearance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results regarding the effect on renal function seems to be in accordance with another series of experiments (34,35). In an ischemic rat model it was found that intra-aortic injections of gadopentetate and diatrizoate, both with an osmolality of about 2.0 osmol/kg water, caused a similar decrease in GFR measured as creatinine clearance.…”
Section: Discussionsupporting
confidence: 91%
“…In an initial pilot study, we did not notice any effect on renal function when the CM were injected into patent renal arteries as had been found in an earlier canine study from our laboratory (44). Therefore, an ischemic period was added to the experiment, a well-established procedure to potentiate the nephrotoxic effect of CM (35,40,45,46). It is well known from both clinical and experimental studies that prior preconditioning is often necessary to make living species susceptible to CM-induced renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dose of iodine atoms appears to have been 10 times that of gadolinium atoms, according to the following: The osmolality of the gadopentetate dimeglumine solution used was reported to be 1,900 mosm/kg and "very close to diatrizoate." These statements, as well as a previous report from the same research group (25), indicate that a 0.5 mol/L gadopentetate dimeglumine solution and a 76% diatrizoate solution (0.97 mmol/mL diatrizoate molecules; Table 1) were used. Thus, only 0.75 mmol (1.5 mL ϫ 0.5 mmol/mL) of gadopentetate dimeglumine molecules (0.75 mmol of gadolinium atoms) seems to have been injected, compared with 2.5 mmol (2.6 mL ϫ 0.97 mmol/mL) of diatrizoate molecules (3 ϫ 2.5 ϭ 7.5 mmol of iodine atoms).…”
Section: Contrast Medium-induced Nephropathymentioning
confidence: 60%
“…The only objection to that results is the short time of determination of HEX urinary excretion after application of ioxaglate, as another researchers (Wellwood et al, 1978) observed increase in urinary HEX excretion three days after administration of gentamycine. However, it was found on the rat model, that ioxaglate induced a smaller increase in urinary HEX excretion than diatrizoate sodium meglumine (Deray et al, 1990). It was reported that PenToXifylline (PTX) seemed to be temporarily effective in reducing proteinuria and stabilizing renal graft function in more t h a n h a l f o f p a t i e n t s a t t h e e n d o f 6 m o n t h f o l l o w -u p i n Chronic Allograft Nephropathy(CAN) (Shu et al, 2007).…”
Section: Hex In Renal Transplantationmentioning
confidence: 93%